The Impact of Enviromental Knowledge and Training Environmental Care Attitudes - Dedeng Abdul Gani Amruloh; Wahyu Yulianto (Budapest International Research and Critics University, 2022)
Changes in the environmental system are quite an urgent challenge and environmental issues can pose major challenges for organizations. Environmentally friendly business organizations become a concern for business practitioners and academics. Vital and strategic aspects in environmental management are human factors and human resource management. Therefore, employees of an organization are expected to care for the environment. This study sets to find out the factors that can improve environmental care attitudes. Environmental care attitudes become a dependent variable whereas independent variables are knowledge of the environment and training. The respondents used in this study are 100 employees from manufacturing in Purwakarta Regency. Employees who become the respondents have a moderately good environmental care attitude. The results of multiple linear regressions show that knowledge of the environment and training impact environmental care attitudes. Employees who have more knowledge about the environment will be more concerned with their environment. Training is also required to improve environmental care attitudes.